Phenolic content and anti-diarrhoeal activity of hydro-alcoholic gauzuma ulmifolia lam. Seed extract (Funded work) - P. SIVAKAMI SUNDARI; SHANAZ BANU; VIMAL JOHN SAMUEL; N. DHANASHREE (International Journal of Pharma and Bio Sciences, 2019)
Diarrhoea is the major cause of infant mortality in most of the developing countries. Inspite of availability of vast spectrum of approaches for management of diarrhoea, majority of people rely on herbal drugs. WHO has also encouraged the studies on the prevention of diarrhoeal diseases by using traditional medicines. As of yet many medicinal plants having claimed the therapeutic value traditionally, are still waiting for scientific validation of their safety and efficacy. In this regard an effort is made to evaluate the antidiarrhoeal efficiency of Gauzuma ulmifolia Lam., a widely growing plant has been reported to possess a number of medicinal properties such as diarrhoea, dysentery, cough , cold, contusions, venereal diseases and also commercial purposes. Traditionally, infusion or decoctions of the seeds are known to possess antidiarrhoeal activity. However, no information was found in the literature about the scientific validation of the anti-diarrhoeal property of the seeds.. In the present study, total phenolic and flavonoid content of the extract was determined. The anti-diarrhoeal effect of hydro-alcoholic (60:40) extract of seeds of Gauzuma ulmifolia was studied against Castor oil induced diarrhoea and Magnesium sulphate induced diarrhoea models in rats using atropine (5mg/kg) as standard. There were significant reductions in faecal output and frequency of droppings when the plant extract of 100, 200 and 400 mg/kg doses were administered orally. All the doses of the plant extracts significantly retarded diarrhoea which may be due to the active phenolic constituent. The result obtained suggests a remarkable anti-diarrhoeal effect of hydro-alcoholic extract and attests its utility in managing a wide range of diarrhoeal conditions.